Given that sin y sin x = 4 and cos y cos x = 3 1 .
And if sin 2 y sin 2 x + cos 2 y cos 2 x = n m , where m , n are co-prime positive integers, find the value of m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did the whole same process 3 times!! I couldn't believe, I would get such an ugly answer!
⎩ ⎪ ⎨ ⎪ ⎧ sin y sin x = 4 cos y cos x = 3 1 ⇒ sin x = 4 sin y ⇒ 3 cos x = cos y ⇒ sin 2 x = 1 6 sin 2 y ⇒ 9 cos 2 x = cos 2 y . . . ( 1 ) . . . ( 2 )
⇒ 9 ( 1 ) + ( 2 ) : 9 sin 2 x + 9 cos 2 x 9 ⇒ sin 2 y ⇒ sin 2 x = 1 4 4 sin 2 y + cos 2 y = 1 4 3 sin 2 y + 1 = 1 4 3 8 ⇒ 1 − 2 sin 2 y = 1 − 2 ( 1 4 3 8 ) ⇒ cos 2 y = 1 4 3 1 2 7 = 1 6 sin 2 y = 1 4 3 1 2 8 ⇒ 1 − 2 sin 2 x = 1 − 2 ( 1 4 3 1 2 8 ) ⇒ cos 2 x = − 1 4 3 1 1 3
Now, we have:
sin 2 y sin 2 x + cos 2 y cos 2 x = 2 sin y cos y 2 sin x cos x + 1 4 3 1 2 7 − 1 4 3 1 1 3 = 3 8 1 5 0 8 − 3 3 9 = 3 8 1 1 6 9 = 4 ( 3 1 ) − 1 2 7 1 1 3
⇒ m + n = 1 6 9 + 3 8 1 = 5 5 0
Missed in calculation mistake ! My solution:
sin
y
sin
x
⟹
1
−
cos
2
y
1
−
cos
2
x
(
2
cos
2
y
−
1
)
−
1
(
2
cos
2
x
−
1
)
−
1
⟹
1
6
cos
2
y
−
1
6
cos
2
x
−
1
6
cos
2
y
=
4
=
1
6
=
1
6
=
cos
2
x
−
1
=
−
1
5
.
.
.
(
1
)
\
\dfrac{Cosx}{Cosy}=\dfrac 1 3,~~~~~\implies~~\dfrac{(2Cos^2x-1)+1}{(2Cos^2y-1)+1}=\dfrac 1 9.\
\implies~~9Cos2x+9=Cos2y+1,~~\therefore~~9Cos2x - Cos2y = -8.........................(2) \
(2)-9(1), ~~gives~~{\color{blue}{Cos2y=\dfrac{127}{143} } }.~~Substituting~this~in~(2),\
9Cos2x= \dfrac{127}{143}-8=\dfrac{127}{143}- \frac {16+7
143]\dfrac{127}{143}{143}.~~~\implies~\color{blue}{Cos2x =\dfrac{16}{9
143} }.\
\dfrac{Sin2x}{Sin2y} + \dfrac{Cos2x}{Cos2y} =dfrac{2Sinx}{2Siny}
\dfrac{Cosx}{Cosy}+\dfrac{\frac{16}{9
143}}{\frac{127}{143} }})
written sinx/siny in terms of cos and plugged the given cosx/cosy in that equation and found the required values
Problem Loading...
Note Loading...
Set Loading...
From the given equations we have 9 sin 2 x = 1 4 4 sin 2 y and 9 cos 2 x = cos 2 y .
It follows that 9 = 9 sin 2 x + 9 cos 2 x = 1 4 4 sin 2 y + cos 2 y = 1 4 4 sin 2 y + ( 1 − sin 2 y )
And so sin 2 y = 1 4 3 8 .
In the same way we get sin 2 x = 1 4 3 1 2 8 , cos 2 x = 1 4 3 1 5 and cos 2 y = 1 4 3 1 3 5
Hence, sin 2 y sin 2 x + cos 2 y cos 2 x = 2 sin y cos y 2 sin x cos x + cos 2 y − sin 2 y cos 2 x − sin 2 x = 4 . 3 1 + 1 4 3 1 3 5 − 1 4 3 8 1 4 3 1 5 − 1 4 3 1 2 8 = 3 8 1 1 6 9
So, m + n = 1 6 9 + 3 8 1 = 5 5 0